The unique characteristics of COVID-19 coagulopathy - Iba T; Levy JH; Connors JM; Warkentin TE; Thachil J; Levi M (Springer Science and Business Media LLC, 2020)
Thrombotic complications and coagulopathy frequently occur in COVID-19. However, the characteristics of COVID-19-associated coagulopathy (CAC) are distinct from those seen with bacterial sepsis-induced coagulopathy (SIC) and disseminated intravascular coagulation (DIC), with CAC usually showing increased D-dimer and fibrinogen levels but initially minimal abnormalities in prothrombin time and platelet count. Venous thromboembolism and arterial thrombosis are more frequent in CAC compared to SIC/DIC. Clinical and laboratory features of CAC overlap somewhat with a hemophagocytic syndrome, antiphospholipid syndrome, and thrombotic microangiopathy. We summarize the key characteristics of representative coagulopathies, discussing similarities and differences so as to define the unique character of CAC.
Keywords: Antiphospholipid syndrome; COVID-19; Coagulopathy; Disseminated intravascular coagulation; Hemophagocytic syndrome; Thrombotic microangiopathy; Betacoronavirus; Blood Coagulation Disorders; Blood Coagulation Tests; COVID-19; Coronavirus Infections; Humans; Inflammation Mediators; Pandemics; Platelet Aggregation; Pneumonia, Viral; SARS-CoV-2